Low-dose norfloxacin and ciprofloxacin therapy worsen leptospirosis in hamster. (January 2017) - Wu, Dianjun; Zhang, Wenlong; Wang, Tingting; Lin, Tao; Jin, Xuemin; Xie, Xufeng; Guo, Jian; Cao, Yongguo; Wu, Rui
Abstract: Antibiotics play an important role in the treatment of leptospirosis. Many antibiotics at appropriate concentrations improved the survival rate and alleviated tissue injury, while, when dosing strategies fall below subtherapeutic levels, worse therapeutic effects are seen. In the present study, we investigated the efficacy of low-dose norfloxacin (10, 20 and 30 mg/kg) and ciprofloxacin (1, 2 and 5 mg/kg) against leptospirosis in a hamster model using Leptospira interrogans serovar Icterohaemorrhagiae. The histopathology and bacterial loads of target organs (liver, kidney and lung) were also studied by treatment with norfloxacin at the dose of 10 mg/kg in this model. Using RT-PCR, the expression of inflammatory factor IL-1β and TNF-α was analyzed by comparing the norfloxacin and untreated group. All untreated animals, serving as a negative control, displayed 50% survival rate, while hamsters treated with norfloxacin at the dose of 10 and 20 mg/kg and ciprofloxacin at the dose of 1 and 2 mg/kg showed a lower survival rate than the untreated group. Furthermore, norfloxacin at the dose of 10 mg/kg increased bacterial loads and aggravated tissue injury of target organs. The delayed induction of IL-1β and TNF-α was found in tissues of norfloxacin group. Our study indicates an increased risk associated with low-dose norfloxacin and ciprofloxacin in leptospirosis. Highlights: The risk associated with low-dose norfloxacin and ciprofloxacin in leptospirosis. Low-dose norfloxacin and ciprofloxacin reduced survival rate. Low-dose norfloxacin increased bacterial loads in target organs. Low-dose norfloxacin aggravated tissue injury of target organs. Low-dose norfloxacin delayed induction of IL-1β and TNF-α in tissues.